Ruminal digestion and chemical composition of new genotypes of buffelgrass (Cenchrus ciliaris L.) - Rocío Morales Rodríguez (Interciencia, 2003)
This study evaluates and compares the dry matter production(TDM), chemical composition and effective degradability ofdry matter (EDDM), crude protein (EDCP) and neutral detergentfiber (EDNDF) of the Nueces hybrid and five new genotypesof buffelgrass growing in Northeastern Mexico. Potentialintake of minerals by cattle consuming the new genotypes wasalso estimated. All grasses were established in a completely randomizeddesign with three replicates in a rain fed experiment.Plants were hand harvested on Nov. 14, 2000 at Nuevo Leon,Mexico. TDM was not significantly different among genotypes.Crude protein content and cell wall and its components (cellulose,hemicellulose, and lignin) were significantly differentamong grasses. Also, EDDM, EDCP, and EDNDF were significantlydifferent among the buffelgrass genotypes. The Nueces hybridhad the highest degradability values; in contrast, PI 2 hadthe lowest values. It seems that high lignin content in newgenotypes may negatively influence nutrient digestion in therumen of sheep. Only the K, Fe and Co contained in allgrasses would be sufficient to meet the requirements of grazingcattle. Data of dry matter production and nutritional dynamics,suggest that the new genotypes PI 1 and PI 4 could be consideredas good substitutes of the Nueces hybrid for grazing ruminantsin northeastern Mexico.